The procedure of tax planning in Ukraine - Melekh, Yaroslav (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
In the article a review is made of the content of tax planning procedure as one of the functions of financial management of a company whose goal is the optimization of taxation with the requirements of civil and tax legislation of Ukraine. The author has researched the features of entity and its basic criteria for optimization — legitimacy, reliability, rationality, autonomy, professionalism and efficiency. The research establishes the basic principles of optimization of taxation of companies and defi nes its stages and types of risks that affect the increase in taxation: information, process, environment, reputation.
Keywords: Ukraina; planowanie podatkowe; zarządzanie finansowe; opodatkowanie